The invitro hippocampal slice technique as a tool for studying the central nervous system - El-Sabban, Farouk; Aziz, Zoriah; Murgan, Vidhya (Faculty of Medicine, University of Malaya, 2000)
The use of brain slice preparations has become increasingly popular among scientists of different disciplines in recent decades for the study of the mammalian central nervous system (CNS) in general and of synaptic phenomena in particular. The in vitro hippocampal slice may be the single most used preparation, among other slices of different parts of the brain areas. The use of brain slices in different experimental work offers certain advantages over the in vivo approaches to the study of the CNS; however, such preparations may have some limitations. This review describes the hippocampal slice technique, explores some of the different types of studies in which it was employed and points out the advantages and limitations of its use.